2021
DOI: 10.3390/antiox10071001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of α-Crystallins in Retinal Neurodegenerative Diseases

Abstract: The chaperone and anti-apoptotic activity of α-crystallins (αA- and αB-) and their derivatives has received increasing attention due to their tremendous potential in preventing cell death. While originally known and described for their role in the lens, the upregulation of these proteins in cells and animal models of neurodegenerative diseases highlighted their involvement in adaptive protective responses to neurodegeneration associated stress. However, several studies also suggest that chronic neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Alpha crystallins function as chaperones that prevent aggregation of client proteins damaged by heat or oxidative stress (Sprague-Piercy et al ., 2021). Alpha crystallins have antiapoptotic and neuroprotective functions in the retina and other neuronal tissues (Zhu and Reiser, 2018; Phadte, Sluzala and Fort, 2021). In the retinal epithelium, both alpha and beta crystallins stabilize the vacuolar-ATPase, thereby protecting against lysosomal dysfunction (Valapala et al ., 2016; Cui et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Alpha crystallins function as chaperones that prevent aggregation of client proteins damaged by heat or oxidative stress (Sprague-Piercy et al ., 2021). Alpha crystallins have antiapoptotic and neuroprotective functions in the retina and other neuronal tissues (Zhu and Reiser, 2018; Phadte, Sluzala and Fort, 2021). In the retinal epithelium, both alpha and beta crystallins stabilize the vacuolar-ATPase, thereby protecting against lysosomal dysfunction (Valapala et al ., 2016; Cui et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…57 α-Crystallins are expressed in many other tissues including the brain where they play a vital role in the central nervous system. 58 Alteration in the proper folding of αcrys is associated with neurodegenerative disorders. 58 A retrospective cohort study conducted in Taiwan concluded that the incidence of Parkinson's disease (PD) was higher in cataract patients.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…58 Alteration in the proper folding of αcrys is associated with neurodegenerative disorders. 58 A retrospective cohort study conducted in Taiwan concluded that the incidence of Parkinson's disease (PD) was higher in cataract patients. 59 Interestingly, the deposition of α-syn aggregates in the retina and disturbances of vision have been suggested by Veys et al as early biomarkers of PD.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…Though typically studied for their structural role in the ocular lens and maintenance of its transparency, it has become increasingly recognized that crystallin proteins play important other functions, including in the retina. In particular, α-crystallins belong to the small heat shock proteins and have gained attention for their neuroprotective properties [ 23 , 50 , 51 ] Over the last decade, several groups have demonstrated that lack of one or both α-crystallin proteins was associated with increased neurodegeneration in diabetic retinopathy, endophthalmitis, uveitis, or retinal tear [ 52 , 53 ]. More recently, intervention studies further supported the neuroprotective potential of α-crystallins by demonstrating that either overexpression or exogenous administration was highly protective [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%